Surface quality of high speed milling of silicon carbide by using diamond coated tool - Iqbal, Mohammad; Konneh, Mohamed; Md Said, Ahmad Yasir; Mohd Zaini, Azri Fadhlan (Trans Tech Publications Ltd., Switzerland, 2014)
The high speed milling of silicon carbide was discussed by using flat end-mill 2 mm in diameter diamond coated tool. Ultra-precision high speed spindle attachment was used to achieve cutting tool rotation speed as high as 50,000 rpm. Special fixture was designed to minimize the chatter on work-piece surface during the machining process. Three cutting parameters were selected as independent variables of the experiments. They were spindle speed, depth of cut and feed rate. The arithmetic mean value of roughness (Ra) was measured on the work-piece surface as the response of the experiment. Result of the experiment shows that the value of surface roughness can be achieved as low as 0.150 μm. Statistical analysis was provided to study the significant of the model, interaction among the cutting parameters and their effects to the surface roughness value.